Demographic variation in space and time: implications for conservation targeting - Morrison, Catriona A; Butler, Simon J; Clark, Jacquie A; Arizaga, Juan; Baltà, Oriol; Cepák, Jaroslav; Nebot, Arantza Leal; Piha, Markus; Thorup, Kasper; Wenninger, Thomas; Robinson, Robert A; Gill, Jennifer A (Royal Society open science, 2022)
The dynamics of wild populations are governed by demographic rates which vary spatially and/or temporally in response to environmental conditions. Conservation actions for widespread but declining populations could potentially exploit this variation to target locations (or years) in which rates are low, but only if consistent spatial or temporal variation in demographic rates occurs. Using long-term demographic data for wild birds across Europe, we show that productivity tends to vary between sites (consistently across years), while survival rates tend to vary between years (consistently across sites), and that spatial synchrony is more common in survival than productivity. Identifying the conditions associated with low demographic rates could therefore facilitate spatially targeted actions to improve productivity or (less feasibly) forecasting and temporally targeting actions to boost survival. Decomposing spatio-temporal variation in demography can thus be a powerful tool for informing conservation policy and for revealing appropriate scales for actions to influence demographic rates.
Keywords: population declines; survival rates; conservation actions; demography; productivity